Mitos suleten: pengaruh dalam pelestarian lingkungan DAS Bengawan Solo - Huda, Khoirul; Alfahmi, Moch Nizam (Universitas Negeri Malang, 2023)
The Bengawan Solo River is the largest river on the island of Java with an area of 16,000 km. The Bengawan Solo watershed is located in two provinces, namely Central Java and East Java. The contribution of the Bengawan Solo watershed is very large in people's lives. Inappropriate waste management and people's belief in the myth of suleten are one of the problems that have an impact on environmental sustainability in the Bengawan Solo watershed area. This research discusses the myth of sulleten which is an environmental problem in communities in the upper middle area of the Bengawan Solo watershed in Madiun Regency. This research method is a qualitative descriptive method with ethnographic study. The research results show that the Suleten myth has an impact on environmental sustainability which causes flood disasters due to river overflows. Sungai Bengawan Solo menjadi sungai terbesar di pulau Jawa dengan luas 16.000 km. DAS Bengawan Solo terletak di dua provinsi yakni Jawa Tengah dan Jawa Timur. Kontibusi DAS Bengawan Solo sangat besar dalam kehidupan masyarakat. Pengelolaan limbah yang kurang tepat dan kepercayaan masyarakat pada mitos suleten menjadi salah satu permasalahan yang berdampak pada kelestarian lingkungan di wilayah DAS Bengawan Solo. Penelitian ini membahas mengenai mitos suleten yang menjadi permasalahan lingkungan di masyarakat wilayah hulu tengah DAS Bengawan Solo di Kabupaten Madiun. Metode penelitian ini adalah metode dekriptif kualitatif dengan studi etnografi. Hasil penelitian menunjukan bahwa mitos suleten memberikan dampak pada kelestarian lingkungan yang menyebabkan bencana banjir akibat luapan sungai.